2016
DOI: 10.1289/ehp.1510352
|View full text |Cite
|
Sign up to set email alerts
|

On the Utility of ToxCast™ and ToxPi as Methods for Identifying New Obesogens

Abstract: Background:In ToxCast™ Phase I, the U.S. EPA commissioned screening of 320 pesticides, herbicides, fungicides, and other chemicals in a series of high-throughput assays. The agency also developed a toxicological prioritization tool, ToxPi, to facilitate using ToxCast™ assays to predict biological function.Objectives:We asked whether top-scoring PPARγ activators identified in ToxCast™ Phase I were genuine PPARγ activators and inducers of adipogenesis. Next, we identified ToxCast™ assays that should predict adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 50 publications
(82 reference statements)
1
118
1
Order By: Relevance
“…A recent report investigating the utility of ToxCast and ToxPi for evaluating adipogenic potential of novel chemicals identified, among others, triphenytlin, quinoxyfen, and fludioxonil; moderate and strong activators in our data series (Janesick et al , 2016). Discordance among the Janesick study results include, but were not limited to, pyraclostrobin and tebufenozide (moderate actives in the hASC assays, inactive in mPPARG reporter assay), as well as zoxamide and spirodiclofen (negative in the hASC screen, positive in mPPARG reporter assays).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent report investigating the utility of ToxCast and ToxPi for evaluating adipogenic potential of novel chemicals identified, among others, triphenytlin, quinoxyfen, and fludioxonil; moderate and strong activators in our data series (Janesick et al , 2016). Discordance among the Janesick study results include, but were not limited to, pyraclostrobin and tebufenozide (moderate actives in the hASC assays, inactive in mPPARG reporter assay), as well as zoxamide and spirodiclofen (negative in the hASC screen, positive in mPPARG reporter assays).…”
Section: Discussionmentioning
confidence: 84%
“…Perhaps the most common cell model employed for investigating chemical perturbation of adipogenesis is the mouse 3T3-L1 cell line (Janesick et al , 2016; Pereira-Fernandes et al , 2013a); a committed adipocyte progenitor that has been invaluable in defining the cellular pathways involved in adipogenesis. An additional transgene assay in Xenopus (Punzon et al , 2013) or whole-organism zebrafish assay (Tingaud-Sequeira et al , 2011) provide additional understanding of PPARG signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of other potential obesogens have been identified that are known to act on pre‐adipocytes or MSCs to promote adipogenic differentiation . It was recently shown that TBT and other chemicals that activate RXR commit MSCs to the adipose lineage by activating RXR, but not PPARγ.…”
Section: Obesogens Reprogram Stem Cell Fatementioning
confidence: 99%
“…Some studies are correlative; for example, chlorinated persistent organic pollutants are associated with increased body mass index and/or type II diabetes in humans in cross-sectional epidemiological studies 46 . Other chemicals induce adipogenesis in cells or activate PPARγ, but have not been tested, in vivo 47-48 . Some EDCs have only been studied in adults while others predispose a developing fetus to subsequent obesity 49 .…”
Section: Evidence Supporting the Existence Of Obesogensmentioning
confidence: 99%